+0  
 
0
276
2
avatar

sqrt(3)cuberoot(2) 

 Jun 21, 2019
 #1
avatar+8873 
+4

\(\sqrt[2]{3}\cdot\sqrt[3]{2}\ =\ 3^{\frac12}\cdot2^{\frac13}\ =\ 3^{\frac36}\cdot2^{\frac26}\ =\ (3^3\cdot2^2)^{\frac16}\ =\ (27\cdot4)^{\frac16}\ =\ (108)^{\frac16}\ =\ \sqrt[6]{108}\)

.
 Jun 21, 2019
 #2
avatar+109345 
+2

√3 *∛2  =

 

(3)^1/2  * (2)^(1/3)  =

 

(3)^(3/6) * 2^(2/6)  =

 

(3^3)^(1/6)  *  (2^2)^(1/6)  =

 

(27)^(1/6) * (4)^(1/6)  =

 

(27 * 4)^(1/6)    =

 

(108)^(1/6)   =

 

6√108

 

 

cool cool cool

 Jun 21, 2019

58 Online Users

avatar